Brain camp - Kim, Susan, 1958-; Klavan, Laurence; Hicks, Faith Erin (New York : First Second, 2010)
Lucas and Jenna are chosen to attend a camp that promises to turn delinquents into high achieving students, but when they arrive, they realize that the camp is not what it seems.
Keywords: Graphic novels; Camps -- Juvenile fiction; Horror tales; Camps -- Fiction; Horror stories; Graphic novels; Camps -- Fiction; Horror graphic novels; Graphic novels